Low-level laser therapy (LLLT) in sites grafted with osteoconductive bone substitutes improves osseointegration - de Oliveira, Guilherme José Pimentel Lopes (2020)
The aim of this study was to evaluate the osseointegration of implants placed in areas grafted with different osteoconductive bone substitutes irradiated with infrared low-level laser therapy (LLLT). Fifty-six rats were randomly allocated into 4 groups: DBB, bone defects filled with deproteinized bovine bone graft (DBB); HA/TCP, bone defects filled with biphasic ceramic made of hydroxyapatite and β-tricalcium phosphate (HA/TCP); DBB-L, bone defects filled with DBB and treated by LLLT; HA/TCP-L, bone defects filled with HA/TCP and treated by LLLT. Bone defects were performed in the tibia of each animal and filled with the different biomaterials. The grafted areas were treated with LLLT (λ 808 nm, 100 mW, ϕ ∼ 0.60 mm) in 7 sessions with 48 h between the irradiations. After the 60-day period, the implants were placed, and the animals were euthanized after 15 and 45 days. The osseointegration and bone repair in the grafted area were evaluated by biomechanical, microtomographic and histometric analyses, and the expression of some bone biomarkers was evaluated by immunohistochemistry analysis. LLLT induced higher degree of osseointegration, which was associated with the greater expression of BMP2 and OCN. LLLT performed in areas grafted with osteoconductive bone substitutes prior to implant placement improves osseointegration.